Format Kepemimpinan Di Tengah Krisis Keteladanan (Studi Analisis Teori Dan Realitas) - Suaidi Suaidi (GURUKU : Jurnal Pendidikan dan Sosial Humaniora, 2023)
A leader is a figure who has the ability to move people or groups of people in an effort to achieve common goals according to planning in an effort to achieve prosperity, harmony, peace. Any form of organization requires a leader who is able to provide comfort for the members of the organization he leads. Criteria and models of leadership have been put forward by many experts in line with the socio-cultural development of humans. This is because the criteria and model of leadership are largely determined by the socio-culture in which the organization and leadership are located. Exemplary for a leader is absolutely necessary because the style of leadership accompanied by the example of a personal leader will have a positive impact on achieving the goals of success of an organization. Therefore, the exemplary nature that emerged from the person of a world leader, namely the Prophet Muhammad SAW, was complemented by the traits inherent in his personality, namely Shidiq, Amanah, Fathonah, and Tabligh. These four traits accompany the success of the Prophet Muhammad, SAW in leading a nation. This study aims to display the leadership format in an effort to achieve the success of an organization. Which includes the nature, style, criteria and exemplary of a leader.